A Case Report on Gingivectomy, For the Management Of Orthodontic Treatment Induced Gingival Enlargement - Pooja Bharadwaj; Anushri Gupta; N Sai Sri Harsha; Nida Malik (Journal of Orofacial Research, 2021)
Gingival enlargement initially known as gingival hyperplasia, is the most common feature of many conditions such as inflammation, drug induced, and systemic conditions such as pregnancy, diseases such as leukemia, treatment induced such as orthodontic treatment induced gingival enlargement. This orthodontic treatment induced gingival enlargement is due to the presence of nickel ions in the orthodontic bands, which result in fibroblastic proliferation. As a result of this enlargement, there is an inability to maintain proper oral hygiene. Gingivectomy is the treatment of choice for this type of gingival enlargement as it helps in the reduction or elimination of pseudopockets, suprabony pockets, which is common in orthodontic induced gingival enlargement. Present case report is on a 21years old female patient who was undergoing orthodontic treatment, and reported to the department of Periodontology for the orthodontic treatment induced gingival enlargement. Gingivectomy was performed for this patient and after one week follow up, the patient shows positive changes as there was no suprabony pocket present.